1999
DOI: 10.1148/radiology.211.2.r99ma27405
|View full text |Cite
|
Sign up to set email alerts
|

Splanchnic Arterial Stenosis or Occlusion: Diagnosis at Doppler US

Abstract: Owing to its high accuracy in the diagnosis of high-grade splanchnic arterial stenosis or occlusion, Doppler US can be used as a screening method to help detect CA or SMA stenosis or occlusion and can reduce the use of unnecessary, invasive angiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Selective catheter angiography is invasive and technically demanding, making it a less than ideal test for MALS. Lim et al 13 proposed Doppler ultrasonography as a reliable screening method to detect stenosis of the celiac artery by measuring end-inspiration and end-expiration velocities.…”
Section: Discussionmentioning
confidence: 99%
“…Selective catheter angiography is invasive and technically demanding, making it a less than ideal test for MALS. Lim et al 13 proposed Doppler ultrasonography as a reliable screening method to detect stenosis of the celiac artery by measuring end-inspiration and end-expiration velocities.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7] Presently, there is no absolute consensus on specific duplex ultrasound (DUS) criteria for the diagnosis of mesenteric/celiac artery stenosis. The present study is based on the largest number of mesenteric duplex/angiography correlations reported to date for the diagnosis of SMA/CA stenosis and validates the optimal duplex velocity with the best positive predictive value (PPV) and negative predictive value (NPV) in detecting Ն50% to Ն70% stenosis of the SMA and CA.…”
mentioning
confidence: 99%
“…With celiac artery stenosis, peak systolic velocities of the celiac artery are elevated to greater than 200 cm/s, and the celiac artery-aortic ratio is greater than 3.0 with both inspiration and expiration. 1 With median arcuate ligament syndrome, the abnormal Doppler findings as described are seen with expiration, but findings are normal with inspiration. 2 Our experience suggests that the celiac artery should be interrogated not only with full inspiration and expiration but also with the patient in the erect position.…”
Section: A Discussionmentioning
confidence: 93%
“…In the erect position, the systolic velocity within the celiac artery decreased to 168 cm/s. 1 The celiac artery caliber returned to normal in the erect position, and the flow pattern was within normal limits ( Fig. 1).…”
Section: Casementioning
confidence: 85%